Strategies used by developers in seeking EnviroDevelopment certification for "sustainable" master-planned residential developments in Victoria, Australia. Issue 3 (25th May 2018) - Green, Ray; Tiwari, Piyush; Rao, Jyoti; Hersburgh, Ricki
Abstract : Purpose: The purpose of this study was to explore strategies used by developers of master-planned housing development projects in Victoria, Australia, for obtaining certification under the Urban Development Institute of Australia's (UDIA) EnviroDevelopment (ED) sustainable development certification programme. To be awarded ED certification, a development must demonstrate that it meets the assessment criteria within at least four of the six ED "leaves". These leaves relate to its performance in terms of energy, water, materials, waste, community and ecosystems. This study explored how developers make choices regarding sustainability features they build into the planning, design and management of their developments to gain the leaves needed for ED certification. Having this certification is valued by developers as it can be used to demonstrate the sustainability credentials of their developments to potential house buyers, the validity of which is backed up by a trusted independent non-profit organisation (UDIA). Design/methodology/approach: The study sought to quantify the preferential weightings of nine developers in selecting ED "leaves" and the strategies they use for meeting the assessment criteria needed to obtain selected ED leaves. This was done using a novel data collection and analysis method, the analytical hierarchical process (AHP), which relies on respondents, in this case, developers of ED certified development projects, making pairwise comparisons between choices of different development factors associated with the different ED "leaves". Findings: The most highly preferred ED leaves were found to be community, energy and ecosystems. "Community facilities" and "on-site transportation" were the two most highly weighted factors associated with the community leaf. Energy, the next most preferred leaf, was most highly weighted on "saving on operational costs" for the consumers (home buyers). Here consumer demand factors seem to be driving preferences. The ecology leaf was the next most preferred, with "existing site conditions" being the most highly weighted factor for this leaf. For sites that already contain significant areas of indigenous habitat, such as wetlands, selecting this leaf would seem to be an attractive, and potentially lower cost, option. Existing ecologically significant natural areas that are preserved, and where necessary enhanced, can be used for marketing purposes and serve in fulfilling planning open-space contribution requirements. The developers were more indifferent to the water, waste and materials leaves; however, the water leaf was rated slightly higher than the other two and was most strongly associated with "recycled water" and opportunities for "water conservation", another example of demand factors driving preferences. Originality/value: The results of this study reveal the preferences of a small sample of developers in terms of how they weigh different factors in making decisions about acquiring sustainability certification for residential master-planned development projects through the UDIA'S ED programme. The findings provide insight into the types of decisions developers make in the process of seeking ED certification, which includes considerations of site characteristics, costs, predicted effectiveness of different interventions and usefulness for marketing and other factors in terms of which ED leaves to pursue and how to acquire them to gain ED certification. The study also tested the AHP method as a methodological tool for addressing this question. Modifications in how data are collected using the on-line survey can be made to allow the method to be more easily used with larger respondent sample sizes. Collection of more focussed data elicited from respondents with specific areas of expertise, for example, specialists in energy, water, landscape architecture and planning, ecology and other relevant areas of knowledge, should also been considered.